Embedding routine hearing health checks within existing Meals on Wheels services – A protocol for the SOUND-BITES Program pilot study - Diana Tang; Jessica Turner; Ugochukwu Eze; John Newall; Kompal Sinha; Carolyn Mee; Claudia Odello; Andrew Blaikie; Bamini Gopinath (PLoS ONE, 2026)
Introduction There is a high prevalence of undiagnosed and untreated hearing loss among older adults. Due to finite resources, task shifting to trained non-specialists is a strategy to improve equity of access to hearing health care. This pilot study aims to implement and evaluate a novel model of hearing care known as the SOUND-BITES program. This will leverage evidence-based mobile health technologies (Arclight otoscopy and Sound Scouts hearing screening app) and partnerships with Meals on Wheels New South Wales and Master of Clinical Audiology students. Methods SOUND-BITES provides a hearing health assessment involving otoscopy using Arclight, hearing screening using the Sound Scouts tablet-based app, and hearing health education to consenting Meals on Wheels clients and their household members. Volunteers from Meals on Wheels and audiology students will be trained to deliver the screening, education and referral components of this program. This pilot study utilises a mixed-methods approach to evaluation. The primary outcomes are program acceptability and feasibility; and secondary outcomes are actions taken by clients to address hearing loss, changes in hearing handicap and cost-benefits six months after program completion. Quantitative data will be collected from a pre- and post-program survey, and qualitative data from an optional post-program interview with clients and volunteers. Findings from the project will be disseminated through peer-reviewed journals and conferences as well as to relevant communities including the Meals on Wheels network.